Comorbid substance use disorders and self-reported substance use in participants with psychotic disorders in the nationwide Finnish SUPER study - Mustonen, Arto (My University, 2025)
Objectives: To examine comorbid substance use disorders (SUD) and self-reported substance use in participants with psychotic disorders. Methods: The study included 9,873 participants from the nationwide Finnish SUPER study with a register-based diagnosis of schizophrenia, schizoaffective disorder, bipolar disorder, psychotic depression, or other psychosis. Register-based diagnoses from 1969 to 2018, including all hospitalizations and specialised outpatient clinic visits, were linked to the data. Comorbid SUD was defined as any SUD diagnosis occurring simultaneously with or after the diagnosis of a psychotic disorder. A questionnaire was used to collect information on current alcohol use (AUDIT-C) and frequency of lifetime drug use. Results: The prevalence of comorbid SUDs in the SUPER study population was 30.8% (n = 3,040). The most common comorbid SUD was alcohol use disorder (80.6%, n = 2,449), followed by a multiple drug or other SUD (33.3%, n = 1,011). Self-reported substance use was notably more common than register-based SUDs: only 53.9% (n = 995) of those reporting current hazardous alcohol use had comorbid SUD. Considering both register-based SUDs and self-reported use, the findings suggest that participants with bipolar disorder and psychotic depression consume more alcohol and fewer drugs compared to those with schizophrenia. Conclusion: This study confirms the high prevalence of comorbid SUDs in individuals with psychotic disorders. Considering self-reported substance use, register-based SUD diagnoses likely underestimate the prevalence of comorbid SUDs. The findings also indicate that individuals with affective psychosis are more likely to consume alcohol, whereas those with non-affective psychosis tend to use drugs more frequently.
Keywords: Psychotic Disorders, Substance-Related Disorders, Schizophrenia